Best n-Term Approximations with Restrictions - Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We determine exact values of the best n-term approximations with restrictions on polynomials used for the approximation of λ, q-ellipsoids in the spaces S^p, μ_φ.